2012
DOI: 10.1590/s0100-29452012000100022
|View full text |Cite
|
Sign up to set email alerts
|

Produção e características físico-químicas dos cachos da videira 'BRS Clara' sob cobertura plástica e sombrite em safra fora de época

Abstract: Devido às condições climáticas favoráveis à ocorrência de doenças fúngicas em uvas de mesa, tem-se buscado a adoção de tecnologias que propiciem a redução nos custos de produção, sendo uma alternativa o cultivo de uvas sob cobertura plástica. O objetivo deste trabalho foi avaliar a produção e as características físico-químicas dos cachos da videira 'BRS Clara' enxertada sobre o porta-enxerto IAC-766 'Campinas', em cultivo protegido durante a safra fora de época, visando à redução da aplicação de fungicidas par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
3
5
0
3
Order By: Relevance
“…After the March-July/2017 cycle, the highest variation in SS content (18.1-20.4 ºBrix) was observed, although the rootstocks did not contribute to significant differences in TA (0.80-0.94 g tartaric acid 100 mL -1 ). Similar values for both variables were also observed in other studies for this cultivar (Yamamoto et al, 2012;Ejsmentewicz et al, 2015). These values are also close to those mentioned for other table grape cultivars (Moreira et al, 2012;Sonego et al, 2002).…”
Section: Quality and Antioxidant Activity Of 'Arizul' Grapessupporting
confidence: 91%
See 2 more Smart Citations
“…After the March-July/2017 cycle, the highest variation in SS content (18.1-20.4 ºBrix) was observed, although the rootstocks did not contribute to significant differences in TA (0.80-0.94 g tartaric acid 100 mL -1 ). Similar values for both variables were also observed in other studies for this cultivar (Yamamoto et al, 2012;Ejsmentewicz et al, 2015). These values are also close to those mentioned for other table grape cultivars (Moreira et al, 2012;Sonego et al, 2002).…”
Section: Quality and Antioxidant Activity Of 'Arizul' Grapessupporting
confidence: 91%
“…As an example, Oliveira et al (2017) reported a SS content of 17.6 ºBrix. This value is indeed close to those (17-19 ºBrix) observed in other studies (Yamamoto et al, 2012;Ejsmentewicz et al, 2015). Regarding the TSS content, there were no significant differences ( Table 6).…”
Section: Quality and Antioxidant Activity Of 'Arizul' Grapessupporting
confidence: 90%
See 1 more Smart Citation
“…5). Colombo et al (2011) and Yamamoto et al (2012) found opposite results. These authors did not find difference in the percentage of fertile buds and number of bunches comparing vineyards under plastic cover and black shading screen.…”
Section: Discussionmentioning
confidence: 89%
“…Feldberg et al (2007), em Mocambinho-MG, constataram que, na média das cinco safras avaliadas para as videiras 'Crimson Seedless', o porta-enxerto 'Paulsen 1103' induziu ao aumento de 50,6% no número de cachos. Portanto, Yamamoto et al (2012) ressalta que a produção das videiras é influenciada por vários fatores, como: características da variedade e do portaenxerto, sistemas de condução, tipos de poda, fertilidade do solo, práticas culturais utilizadas em cada região e condições edafoclimáticas.…”
Section: Discussionunclassified